Super Bundles - Claudio Carmeli; Rita Fioresi; V. S. Varadarajan (Universe, 2018)
In this paper we give a brief account of the main aspects of the theory of associated and principal super bundles. As an application, we review the Borel-Weil-Bott Theorem in the super setting, and some results on projective embeddings of homogeneous spaces.